Reciprocal Teaching Strategy to Improve Students’ Reading Comprehension: Action Research - Parameswara, Camelia; Wicaksono, Andri; Herlisya, Destia (IJLHE: International Journal of Language, Humanities, and Education, 2022)
The objectives of this research were to improve the students’ learning activity and reading comprehension by using the Reciprocal Teaching Strategy. This strategy helps students with four steps, such as predicting, questioning, clarifying, and summarizing. In this research, the writer used Classroom Action Research as the design in collecting the data. The research implementation of research was in two cycles. The sample of this research was in one class only with 27 students. The writer used an observation sheet and reading test in form of was multiple choice and consisted of 40 questions, it aimed to get the score of students’ reading comprehension and used observation sheet for the students’ learning activity. The findings of this research showed Reciprocal Teaching Strategy was successful to improve students’ learning activity and reading comprehension. It can be seen from the average score of students’ learning activity and reading comprehension. The average score of students’ learning activity was increased from the first cycle 6.66 while in the second cycle 7.67, it was from less active to active criteria. Then, it was found that the average score in cycle 1 was 67.4 or 51.85% of students who passed Minimum Mastery Criteria while in cycle 2 was 76.5 or 85.19% of students who passed Minimum Mastery Criteria. Therefore, the implementation of Reciprocal Teaching Strategy was successful to be used in improving the students’ learning activity and reading comprehension in the tenth grade of SMKN 9 Bandar Lampung in the academic year of 2022/2023.